Comparison of donor site complications of supra- versus subfascially harvested anterolateral thigh perforator free flaps: A meta-analysis. Issue 1 (January 2020) - Su, Xing-Zhou; Yin, Shou-Cheng; So, Hyon Il; Wang, Shuai; Zhang, Ze-Liang; Xu, Zhong-Fei; Sun, Chang-Fu
Abstract: Objective: This study aimed to compare the complications at the donor site of supra- versus subfascially harvested anterolateral thigh perforator free flaps. Method: We searched PubMed, Web of Science, EMBASE, the Chinese BioMedical Literature Database (CBM) and the Cochrane Library until December 31, 2018, to identify studies that compared complications at the donor site of the supra- versus subfascially raised anterolateral thigh perforator free flaps. Two authors individually extracted the data and performed the quality assessments. Skin grafting, the rate of poor healing in the donor site, dysfunction at the donor site and sensory functions at the donor site were evaluated. Result: Seven studies with a total of 525 patients were included in our analysis. No significant differences were found regarding skin grafting and sensory functions between the 2 groups. However, in regard to the rate of poor healing and dysfunction at the donor site, the SPF group showed significantly better outcomes than the SBF group after the operation. Conclusion: Our meta-analysis suggested that, in regards to skin grafting and sensory recovery, the SPF and SBF groups were similar. With regard to donor site healing and functional recovery, the SPF group exhibited better outcomes than the SBF group.